Why We Must Talk About Institutional Corruption to Understand Wrongdoing in the Health Sector; Comment on "We Need to Talk About Corruption in Health Systems" - Marianna Fotaki (Kerman University of Medical Sciences, 2020)
While various forms of corruption are common in many health systems around the world, defining wrongdoing in terms of legality and the use of public office for private gain obstructs our understanding of its nature and intractability. To address this, I suggest, we must not only break the silence about the extent of wrongdoing in the health sector, but also talk differently about corruption in general, and corruption in healthcare specifically. I propose adopting the notion of institutional corruption (IC) developed by Thompson and Lessig, as divergence from the original purpose of the institution, which may not be illegal but may nevertheless cause harm to people who depend on it by creating perverse dependencies and compelling individuals to act against its core purpose. Such work is much needed to provide in-depth accounts of how external political and legislative pressures enable corruption in healthcare systems. I also argue for bringing together insights from various research domains and levels of analysis to capture why and how corruption becomes systemic, deeply embedded, and intractable.